Rescue of protein dyshomeostasis in hippocampal astrocytes from an Alzheimer’s disease mouse model by stabilizing ER-mitochondrial interactions at a 20 nm distance - Giulia Dematteis; Chunmei Gong; Justyna Malecka; Elisa Tonelli; Armando Genazzani; Laura Tapella; Anna Maria Eleuteri; Dmitry Lim; Laura Bonfili (Alzheimer’s Research & Therapy)
Abstract Background Alzheimer’s disease (AD) is the major age-related form of dementia in which dysfunctional ubiquitin-proteasome system (UPS) and autophagy represent primary mechanisms leading to accumulation of misfolded proteins, dysfunction of astroglial cells, neuroinflammation and neurodegeneration. Alterations of the endoplasmic reticulum (ER)-mitochondria contact sites (MERCS), specifically the shortening of the distance between the organelles, was proposed as a key mechanism of cell dysfunction in AD. However, its link to the impairment of the proteolytic system in AD remains unexplored. Methods We used, as a model, hippocampal astrocytes from 3xTg-AD mice expressing either control plasmid or synthetic linkers stabilizing ER-mitochondrial interaction at 10 nm (10 nm-EML) or at 20 nm (20 nm-EML). Alternatively, astrocytes were treated with mitochondrial Ca2+ uptake inhibitor benzethonium chloride or activator amorolfine. We used Western blot to assess protein expression and specific enzymatic activity tests for the analysis of proteasomal, autophagic and lysosomal activities. Single cell fluorescent Ca2+ imaging, using 4mtD3cpv probe targeted to the mitochondrial matrix, was used to assess mitochondrial Ca2+ uptake. Results Stabilization of MERCS at 20 nm (20 nm-MERCS), which promotes mitochondrial Ca2+ uptake, rescued protein ubiquitination, UPS composition and activity. Immunoproteasome components β2i and β5i, upregulated in AD astrocytes, and INFγ, a master-regulator of UPS remodelling in inflammatory conditions, were also rescued. Autophagic markers beclin 1, LC3II and p62, and lysosome-related marker cathepsin B, all upregulated in AD astrocytes, were significantly reduced, while autophagic flux was rescued, by stabilizing 20 nm-MERCS. Furthermore, stabilization of 20 nm-MERCS fully rescued previously reported deficit of mitochondrial Ca2+ uptake. Strikingly, application of a mitochondrial Ca2+ uptake positive modulator, amorolfine, partially rescued pathological remodelling of UPS and autophagy, suggesting that both mitochondrial Ca2+-related and Ca2+-unrelated mechanisms play a role in the beneficial effect of 20 nm-MERCS stabilization on protein dyshomeostasis. Conclusions Our results suggest that disruption of ER-mitochondrial interaction is a key factor for AD-related dysregulation of protein degradation and provide a proof that stabilization of MERCS at a defined distance and/or pharmacological rescue of mitochondrial Ca2+ uptake represent valuable strategies for the development of future anti-AD therapy.